Wiring the nation: telecommunication, newspaper-reportage, and nation building in British India, 1850-1930 - Mann, Michael (London: Oxford, 2017)
Generally, the history of telegraphy has been written from a technological perspective. In contrast, this book specialises on the social, cultural, and political consequences of the telegraph. British India between 1850 and 1930 serves as an example in how far and to what extent telecommunication influenced, shaped and transformed the British Indian multiple public spheres as to the emergence of an all-India public sphere after the turn of the nineteenth century. As an intrinsic part of this transformation, newspaper reportage in British India underwent massive changes as that was the case in many other countries of the world in the Age of Globalisation. It is this global context which places the study not just in an Indian national context, but in an international setting. Against this background it is also argued that the emergence of the Indian national movement took place in a worldwide connected and entangled communication context that deeply influenced the press landscape of British India as it did the imagination of an Indian nation in an internationally organised world.
Keywords: Telegraph India; Press India; Nation Building India; Social Sciences